LEKSIKON BUDAYA DALAM TRADISI KHITANAN PADA MASYARAKAT MELAYU SAMBAS - Eldine, Rezki Barida; Syahrani, Agus; Muzammil, Ahmad Rabi’ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to record the existing lexicon in the circumcision tradition (besunat) of the Sambas Malay community, especially in the pre- implementation, implementation, and post-implementation processes, as well as produce supplementary teaching materials for Indonesian language learning based on the cultural lexicon in the circumcision tradition (besunat) in the Sambas Malay community. The theory used is the theory of anthropolinguistics. The method used is a descriptive method with a qualitative form. The source of data in this study is the Sambas Malay community. Data collection techniques are observation, interviews, recording techniques, note-taking techniques, documentation. This study produced 53 data consisting of 4 pre-implementation lexicon, 1 implementation lexicon, 4 post-implementation lexicon, 23 lexicon in the form of tools used, 8 lexicon in the form of materials used, 6 lexicon in the form of food served, 4 lexicon in the form of the actors involved, 1 lexicon in the form of time, 2 lexicon of cultural objects used. The form of the lingual unit there are 29 lexicon in the form of monomorphemic form, 4 lexicon in the form of polymorphemic form, 19 lexicon in the form of endocentric phrase, the meanings found in this study were 53 in the form of lexical meaning, 27 lexicon in the form of culturalmeaning. The form of Indonesian language learning text produces descriptivetext.